2018
DOI: 10.1021/acssensors.8b00168
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Wearable Sensor for Electrochemical Analysis of Perspiration Glucose

Abstract: We report a nonenzymatic wearable sensor for electrochemical analysis of perspiration glucose. Multipotential steps are applied on a Au electrode, including a high negative pretreatment potential step for proton reduction which produces a localized alkaline condition, a moderate potential step for electrocatalytic oxidation of glucose under the alkaline condition, and a positive potential step to clean and reactivate the electrode surface for the next detection. Fluorocarbon-based materials were coated on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 75 publications
(102 reference statements)
0
83
0
Order By: Relevance
“…We have demonstrated in our previous work 6 that introducing a preconditioning step can solve issues related to peak suppression/overlap, by electrochemical cleaning of the electrode surface, creating defect sites through the removal of carbon or reducing various functional groups, which seems to be beneficial for the electrochemical response. Zhu et al 24 reported that an electrode pretreatment by applying a negative potential creates alkaline conditions near the electrode surface which may explain the increase and shift in the peak signal upon pretreatment at pH 7.0. To check if the strategy is applicable to heroin samples, SWV with a preconditioning step was performed at pH 7.0 and at pH 12.0.…”
Section: Electrochemical Screening Of Heroin and Mixing Agents At Ph 70mentioning
confidence: 99%
“…We have demonstrated in our previous work 6 that introducing a preconditioning step can solve issues related to peak suppression/overlap, by electrochemical cleaning of the electrode surface, creating defect sites through the removal of carbon or reducing various functional groups, which seems to be beneficial for the electrochemical response. Zhu et al 24 reported that an electrode pretreatment by applying a negative potential creates alkaline conditions near the electrode surface which may explain the increase and shift in the peak signal upon pretreatment at pH 7.0. To check if the strategy is applicable to heroin samples, SWV with a preconditioning step was performed at pH 7.0 and at pH 12.0.…”
Section: Electrochemical Screening Of Heroin and Mixing Agents At Ph 70mentioning
confidence: 99%
“…Non-enzymatic electrochemical glucose sensors possess the advantages over enzymatic sensors in terms of low cost, good thermal stability and satisfactory reproducibility 21,22 . Non-enzymatic electrochemical detection sensor is based on the oxidize glucose to a detectable electrochemical signal, which directly occurs on the electrode surface by an electric current effect 23 . For the non-enzymatic glucose sensor, the design and fabrication of the active materials play a key role in the sensing performances since it can efficiently catalyze and oxidize glucose to produce gluconolactone and can free from the operating conditions 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of molecules and ions in body fluids, electrochemical approaches are commonly employed. To detect the concentration of some molecules, such as glucose, [ 30 ] alcohol, [ 31 ] and lactate, [ 32 ] the corresponding enzymes (i.e., glucose oxidase, alcohol oxidase, and lactate oxidase) act as the sensing elements via the specific reaction. The enzymes catalyze the zymolyte, during which electron transfer would happen.…”
Section: Basic Composition Of Wearable Sensorsmentioning
confidence: 99%